2012
DOI: 10.1089/aid.2011.0307
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection in Men Who Have Sex with Men in Lima, Peru

Abstract: Human papillomavirus (HPV) infection among men who have sex with men (MSM) is the primary risk factor for anal cancer. Of 105 Peruvian MSM examined, 77.1% were infected with HPV; of these 79.0% were coinfected with two or more types and 47.3% were infected by a carcinogenic type. HPV types 53, 6, 16, and 58 were the most frequent HPV infections detected. High-risk HPV type infection was associated with sex work, HIV status, and having rectal chlamydial or gonorrheal infection. These findings support broadening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 36 publications
5
31
0
3
Order By: Relevance
“…From the 18 eligible studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] , 7 (38.9%) were conducted in the United States (1), in Brazil (3), in Argentina (2), in Peru (1), 5 (27.8%) in Europe, and 6 (33.3%) in Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 18 eligible studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] , 7 (38.9%) were conducted in the United States (1), in Brazil (3), in Argentina (2), in Peru (1), 5 (27.8%) in Europe, and 6 (33.3%) in Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the complete reading of the 18 eligible papers for the systematic study [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] , it was found that the location where HPV is most predominant is the cervical area, the vulva, the vagina, and the anus, since they are associated with chronic infections, preceded by non-malignant precursor lesions, like the cervical squamous intraepithelial lesion (CSIL) and the anal squamous intraepithelial lesions (ASIL), with predilection being shown for the zone of cellular transition of glandular squamous cells, seeing that both have common biological characteristics, including histopathological aspects.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, self-reported current STI symptoms was highly correlated with increased risk of having visible anogenital warts, consistent with other studies reporting a greater likelihood of HPV infection with clinically diagnosed STIs. 24,28 Older age at first episode of anal intercourse was strongly correlated with having visible anogenital warts. This could be due to several factors including improved safe-sex education among younger MSM, lower frequency of anal intercourse acts among those younger than 14 years compared with older MSM, or the development of HPV-specific immunity due to early exposure among those with earlier sexual debut.…”
Section: Discussionmentioning
confidence: 97%
“…23 Although data on HPV prevalence in these populations are scarce, a recent study of 105 MSM recruited from an urban STI clinic found that 77.1% tested positive for HPV by polymerase chain reaction on anorectal samples. 24 In this crosssectional study, we examined factors associated with visible anogenital warts (overall and by anatomical site), including those that are known to confer increased risk for HIV infection, among HIV-uninfected MSM and transwomen in Lima, Peru.…”
mentioning
confidence: 99%
“…One study of 105 MSM from an inner-city STI clinic in Lima found that 77.1% were infected with anogenital HPV and 43% were infected with a carcinogenic type; high-risk HPV type infection was associated with sex work, HIV status and rectal chlamydial or gonorrhoeal infection. 24 Another study of HPV prevalence among 200 Peruvian MSM found the seroprevalence of HPV types 6/11/16/18-for which the quadrivalent HPV vaccine confers protectionwas 64.3% and 93.8% for HIV-negative and HIV-positive MSM, respectively. 25 While both studies included information related to sexual practices, identity and roles, the analyses conducted do not allow side-by-side comparisons of these factors and HPV, information which could inform HPV surveillance, prevention and treatment for Latino MSM.…”
Section: Open Accessmentioning
confidence: 99%